Public order offences - Iñigo Gordon Benito (Oñati Socio-Legal Series)
As an area of law in the UK, public order offences are almost entirely useless on social media. This set of offences (ss. 4, 4A and 5 of the Public Order Act 1986) was aimed to address any behaviour or expressive activities, either oral or written, carried out in a context of physical proximity to the victim. In principle, the foundational base of public order offences runs the risk of becoming blurred if we extend their applicability to hateful messages online and, therefore, to any impersonal way of acting. Consequently, only 13% and 14% of the hate crimes committed online in 2016/17 and 2017/18 in England & Wales involved public order offences. Therefore, there is a certain resistance based on the adequacy of these offences to the online environment without requiring the message to be audible or visible to someone, as a matter of immediacy/proximity. We will explain how this glimmer of hope has lasted over time amid fierce opposition to broaden the scope of application of public order offences beyond traditional public forums, such as disturbances triggering in a city's main square.